Case studies as one of the communication methods of foreign language teaching law students - Голубнича, Людмила Олександрівна (Problems of legality, 2016)
The article deals with the problem of «case» in methods of teaching foreign languages. Considerable attention is paid to finding out features of using case studies during training law students a foreign language in order to maximize communication approach of classes. The papers contain examples of the use of case studies in classes of law students to train speech (monologue, dialogue speech) and speech preparation (formation of lexical and grammatical skills) activities.